Workshop on Creating Game Using Scratch as an Activity to Support the Vision of Indonesia Gold 2045 at SMK Negeri 5 Pekanbaru - Suci Ramadona; Risky Amelia; Wiranda Gilang (Institut Teknologi Nasional, Bandung, 2022)
In order to welcome creative industries that synergize with technology, the Indonesian government has begun to prepare a vision for the golden Indonesia 2045. One of its pillars is the development of Indonesian human resources along with the mastery of science and technology. To realize this vision, superior human resources possessing creativity, critical thinking, communication, and collaboration skills are needed. The right method in character building is the development of potential skills from early age with the help of the world of education. One of the formal educational institutions building students’ characters to be skillful and competitive workforce, and developing entrepreneurial skills from an early age is vocational high school (SMK). Therefore, introduction of programming using Scratch to students of SMK Negeri 5 Pekanbaru is a learning method that is expected to develop the desired HR characters. Moreover, simple game creation training using Scratch can provide an overview of the use of simple coding as an introduction to how technology works. The activities were carried out in 4 method models, namely planning, action, observation, and reflection. The success rate of this activity is measured based on the results of score comparison between pre-test and post-test. The post-test results showed an increase of 96.67% compared to the participants’ initial understanding.